Applying Multicultural Education at School, or How to Lead Pupils to Tolerance - Mária Vargová (Ignatianum University Press, 2019)
Multicultural education is a cross-cutting theme in the state educational programme ISCED 1 - primary education. In primary education, multicultural education can be taught as a separate subject or it can be included in other ongoing subjects. When applying multicultural education it is also important that the teacher doesn't have prejudices against any ethnic group or nationality. He/she should also use appropriate methods that lead to pupils becoming more tolerant.